Professional Ethics of Social Entrepreneurs: The Perspective of Christian Personalist Ethics - Zadroga, Adam (Verbum Vitae, 2021)
The aim of the article is to indicate and describe the normative assumptions of the professional ethics of social entrepreneurs. The innovative nature of the proposed concept consists in taking into consideration the perspective of Christian personalist ethics. It is a theory of morality which includes considerations for the biblical and theological view of man, emphasizing above all their personal dignity. Referring to the principal axioms of this ethical doctrine allows for a presentation of a proposal of ethical principles and moral virtues – adequate to the mission, tasks, and vocation of social entrepreneurs. The article discusses the following issues: the essence of Christian personalist ethics, the mission and tasks of social entrepreneurs, the motivation and vocation of social entrepreneurs, ethical aspects of leadership in social enterprises, as well as the ethical principles and moral virtues of social entrepreneurs. A methodology characteristic of normative philosophical ethics and moral theology was applied. The results of the analysis of the methodically selected literature on the subject were processed by means of conceptual work, which allowed us to describe the professional ethics of social entrepreneurs from the point of view of Christian personalist ethics. Christian personalist ethics makes a valuable and original contribution to the description of the normative determinants of social entrepreneurship. The analysis of the mission and tasks of social entrepreneurs shows that they create social structures and processes that affirm the dignity of marginalized people and restore their capacity to participate in social and economic life.